Cenário para celebração: verificação de aspectos turísticos e patrimoniais do centro histórico de Garibaldi/RS pela metodologia Sistema P. - Langaro, Carmen Silvia (My University, 2025)
This study was conducted for the Master's dissertation in Tourism and Hospitality at the University of Caxias do Sul (UCS). The line of research is Tourism, Hospitality, Culture and Education, with a focus on cultural heritage. It is part of a theoretical-methodological field that conceives cultural heritage as a strategic resource for tourism, but also as an expression of memory, identity, and community participation. The territory researched is the Centro Histórico de Garibaldi - CHG (Historic Center of Garibaldi), a city of 35 thousand inhabitants located in the Northeast region of Rio Grande do Sul. The colonization by European immigrants, starting in 1875, and the production of sparkling wine, are relevant elements of intangible heritage. Among the tangible assets, the houses remaining from the immigration and later generations stand out, represented by examples concentrated in the historic center. The research's general objective was to evaluate the tourist and heritage aspects of the historic site using indicators from the Sistema P methodology (Brito, 2009; Brito, 2019; Iphan, 2020). Changes were made to adjust the scope to the nature of the territory and the study. As a result, based on the methodology's conceptual framework, the Centro Histórico de Garibaldi obtained maximum scores in almost all variables, which measured aspects such as the integrity, authenticity, and vitality of the heritage, basic tourism services at the historic site and surrounding area, the CHG's management policies and practices, and the information system adopted. Further studies are recommended to add sustainability indicators to the P System, as well as to assess the economic valuation of the CHG's built heritage. [resumo fornecido pelo autor]
O presente estudo foi realizado para fins da dissertação de Mestrado em Turismo e Hospitalidade pela Universidade de Caxias do Sul – UCS. A linha de pesquisa é Turismo, Hospitalidade, Cultura e Educação, com foco no patrimônio cultural. Insere-se em um campo teórico-metodológico que concebe o patrimônio cultural como recurso estratégico para o turismo, mas também como expressão de memória, identidade e participação comunitária. O território pesquisado é o Centro Histórico de Garibaldi - CHG, município de 35 mil habitantes localizado na Região Nordeste do Rio Grande do Sul. A colonização por imigrantes europeus, a partir de 1875, e a produção de vinhos espumantes, são elementos relevantes do patrimônio imaterial. Entre os bens materiais, destaca-se o casario em alvenaria remanescente da imigração e de gerações posteriores, representado por exemplares que se concentram no centro histórico. A pesquisa teve por objetivo geral avaliar aspectos turísticos e patrimoniais do sítio histórico, por meio de indicadores extraídos da metodologia Sistema P (Brito, 2009; Brito, 2019; Iphan, 2020). Alterações foram efetuadas para ajustar o escopo à natureza do território e do estudo. Como resultados, à luz conceitual da metodologia, o Centro Histórico de Garibaldi obteve pontuação máxima em quase todas as variáveis, que mediram aspectos como as condições de integridade, autenticidade e vitalidade do patrimônio, serviços turísticos básicos no sítio histórico e no entorno, as políticas e práticas de gestão do CHG e o sistema de divulgação adotado. Sugere-se a realização de novos estudos que agreguem indicadores de sustentabilidade ao Sistema P, bem como de valoração econômica do patrimônio edificado do CHG. [resumo fornecido pelo autor]
Keywords: Turismo cultural - Garibaldi (RS); Patrimônio cultural; Centros históricos; Heritage tourism - Garibaldi (Brazil); Cultural property; Historic districts